2022
DOI: 10.3390/ani12060676
|View full text |Cite
|
Sign up to set email alerts
|

A Culture-Based Study of Micromycetes Isolated from the Urban Nests of Grey Heron (Ardea cinerea) in SW Poland

Abstract: There are many positive relationships between micromycetes and birds: They can spread fungal spores, and fungi facilitate cavity woodpecker excavation by preparing and modifying excavation sites. In turn, bird nests are mainly a source of potentially zoopathogenic fungi. The Wrocław city centre hosts the biggest grey heron breeding colony in Poland with at least 240 breeding birds pairs. To assess the possible public health risks associated with bird nests, the goal of the present study was to identify cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…P. album and P. hyalophaea were the most frequently isolated species overall; however, when taking into account only fungi isolated at 24 °C, P. cumulodentata and P. sumatraense were the most abundant on PDA and YPG media, respectively. It can be concluded that the effectiveness of a successful, culture-based mycological analysis depends, among other things, on combining diverse conditions, such as different temperatures and types of media [ 66 ]. Nevertheless, only a few reports regard P. cumulodentata , including its original description in 1976 [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. album and P. hyalophaea were the most frequently isolated species overall; however, when taking into account only fungi isolated at 24 °C, P. cumulodentata and P. sumatraense were the most abundant on PDA and YPG media, respectively. It can be concluded that the effectiveness of a successful, culture-based mycological analysis depends, among other things, on combining diverse conditions, such as different temperatures and types of media [ 66 ]. Nevertheless, only a few reports regard P. cumulodentata , including its original description in 1976 [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that most of the mycotoxins present in the feed are excreted with droppings in birds [ 33 , 34 , 35 ]. Recently, there have been significantly fewer cases of consumption of large amounts of mycotoxins by birds than 10–20 years ago, since strict quality control of feed is organized in developed countries.…”
Section: Mycotoxins In Poultry Manurementioning
confidence: 99%
“…Some of these opportunistic filamentous fungi present in the oral cavity of nestling black kites have been found in nests of birds (including raptors), such as Fusarium sp., Penicillium sp., Alternaria sp., M. hiemalis, and M. circinelloides (Kornillowicz-Kowalska et al, 2011;Kornillowicz-Kowalska and Kitowski, 2018;Ogórek et al, 2022). In addition to growing on and colonizing plant fragments of the bird nests (Ogórek et al, 2022), some of the potentially phytopathogenic and zoopathogenic fungi identified in nestling black kites have also been detected in bird droppings, such as Pennicilium sp., Mucor sp. and Rhizopus sp.…”
Section: Anthropogenic and Natural Environmental Factors Have A Great...mentioning
confidence: 99%